PEMBUATAN GAME SIMULASI LIVING WITHOUT MONEY MENGGUNAKAN UNITY - Dewi Triani; viny Christanti Mawardi (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Simulation game "Living Without Money" is a series of life simulation game the theme story of a fictional essay. This game has a background story i.e. the player plays as the grandson of a grandmother who lived through the Bethany way, raising and barter with residents of the village of Verdon. Barter trading process is done with a pretty unique. The game is played using the Android mobile device. How to play this game fairly easily. The player can touch screen smartphone for redirecting a folder properly and start the game. Players simply run the mission stated on the menu quest to ascend the next level. This game is interesting enough to be played by all circles both children, teens and adults. Game testing is done through three phases namely blackbox testing, alpha testing and beta testing. Through the blackbox testing, all of the modules contained in the game works and runs fine. Alpha testing is testing a game that made according or not before given to the user. After going through the stage of beta testing, the game was summed up by the respondent related that argues the game is quite interesting and worthy played all ages.